Program Kuliah Kerja Nyata (KKN) Sebagai Instrumen Pembangunan Berkelanjutan dalam Menciptakan Desa Bersih, Sehat, dan Mandiri di Desa Cinangela Kecamatan Pacet Kabupaten Bandung: Pengabdian - Lina Yuliyani; Neneng Nurbaeti Amien; Fajri Rama Jaenudin; Najla Safiya Ajani Syah; Bagus Nur Ikhwanudin; Cintia Maulida; Muhamad Imanudin Wahid; Muhamad Naufal Rabbani; Nadya Ayuni Widiani; Noni Nur Nazmi Fadhlilah; Riyanti Ramdhani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Service Program (KKN) represents a form of higher education’s Tri Dharma mission that integrates academic knowledge with the real needs of society. This article explores the implementation of KKN Group 32 of Universitas Muhammadiyah Bandung in Cinangela Village, Pacet Subdistrict, Bandung Regency, under the theme “Community Empowerment Towards a Smart, Independent, Sustainable, and Progressive Village (CEMARA).” The program was designed to address the village’s main challenges, namely waste management, limited health services, and the need to improve educational quality. The implementation method was participatory, involving observations, community leader discussions, and village deliberations, which resulted in the core program of integrated waste management (biopores and rocket stove), free health check-ups, and supporting programs in education and psychoeducation. The outcomes demonstrated increased community awareness of environmental cleanliness, health, and strengthened educational capacity for children and adolescents. In conclusion, KKN proves to be effective as an instrument of sustainable development through an integrative approach encompassing environment, health, and education, while fostering community independence.